Reliability and Construct Validity of 3 Psychometric Trust Scales for Women Seeking Substance Abuse Treatment in a Community Setting. Issue 3 (July 2020) - Cockroft, Joshua D.; Adams, Susie M.; Matlock, Deondria; Dietrich, Mary S.
Background: Women with a history of substance use disorder (SUD) constitute a unique population with gender-specific needs in treatment. Most notable is high rates of prior trauma and the need for a trauma-informed care framework. Given theoretical links between trauma and interpersonal trust, understanding quantitatively how trust may impact outcomes for women in this population requires confirmation of validity of existing psychometric instruments. Objective: This study sought to confirm reliability and construct validity of the Rotter Interpersonal Trust Scale, Wake Forest Trust in Physician Scale, and the Revised Health Care System Distrust Scale (RHCSDS) for use in women with a history of SUD seeking treatment in a community-based setting. Methods: A total of 301 participants were enrolled between August 2017 and March 2018 at an urban, community-based residential substance abuse treatment program in the mid-South. Participants were given an electronic survey containing questions about demographics/clinical characteristics, the Rotter, Wake Forest, and RHCSDS scales, Socially Desirable Response Five-Item Survey (SDRS-5), and the Adverse Childhood Experiences (ACEs) questionnaire. All participants also completed a modified protocol of the "Trust Game." Statistical analysis was completed for each trust scale in regard to scale means and distribution, internal consistency, interscale correlation, and scale correlation to the ACE score. Results: Results confirm statistically significant ( P  < .001) differences in global trust and trust of health care providers compared with general population samples in prior studies. Internal consistency of scales is comparable to reliability testing in prior studies (α > .70 for all scales). Interscale correlation between individual scales is statistically significant, with the strongest relationship between the 2 health care–specific scales ( r  = −.740, P  < .001). There was a weak, negative correlation between the ACE score and interpersonal trust ( r  = −.135, P  = .019). Individual scales do not have statistically significant correlation with "Trust Game" scores. Discussion: Findings suggest reliability and construct validity of scales for use in this population.